Conservation implications of cascading effects among groups of organisms: The alien tree Robinia pseudacacia in the Czech Republic as a case study. (June 2016) - Reif, Jiří; Hanzelka, Jan; Kadlec, Tomáš; Štrobl, Martin; Hejda, Martin
Abstract: Invasions of non-native plants often result in impoverished local communities; however, their cascading effects along food chain remain unknown. Here we investigated how the alteration of food resources and habitat structure due to the invasion of an alien tree affects the species richness of habitat specialist and generalist birds. During 2014, we sampled forest stands of the invasive Robinia pseudacacia and control stands of native trees in the Czech Republic (central Europe). Specifically, we performed intensive breeding bird counts and assessed moth diversity as a key food resource for breeding birds and, described the habitat structure of sampled stands. Compared to native tree stands, stands of R. pseudacacia had a lower species richness of habitat specialist birds, a higher species richness of habitat generalist birds, a lower diversity of moths, a less continuous canopy and a more developed shrub layer. Then we related bird species richness to moth diversity and descriptors of habitat structure. Moth diversity was the only variable significantly related to the species richness of habitat specialist birds, while the species richness of habitat generalist birds was related solely to the local habitat structure. Specialists were thus limited by a less diverse food supply in the invaded stands, most likely due to the absence of some arthropod species. In contrast, generalists were ecologically more flexible and exploited new breeding opportunities created by a shrub layer in the invaded stands. Our study thus provides evidence that impacts of an invasive tree scale up across trophic levels. Highlights: We surveyed birds and their insect food in invaded and native forest stands. Specialists were more species-rich in native stands, generalists showed the opposite. Species richness of specialists was limited solely by the number of moth species. Species richness of generalists was limited solely by the habitat structure. These two different mechanisms may drive biotic homogenization of local communities.